Studi Psikolinguistik Tentang Persepsi Bunyi dalam Pembelajaran Bahasa Arab di SMA Negeri 3 Medan - Syarifah Aulia; Siti Nurfadilla; Rizky Saifurrahman; Sahkholid Nasution (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the perception of sounds in Arabic language learning at SMA Negeri 3 Medan. Sound perception refers to students' ability to recognize and produce sounds in Arabic, which often differ from sounds in the Indonesian language. This research identifies phonological difficulties experienced by students, the factors influencing their sound perception, and the teaching methods employed to address these challenges. The research methodology used is qualitative with a case study approach, involving observations, interviews, and phonology tests with 30 students and several Arabic teachers at SMA Negeri 3 Medan. The results show that students face major difficulties in distinguishing and producing certain sounds, such as the letters